Survey Study on Fraud Prevention Disclosure Measurement at State Islamic Universities in Indonesia - Wulandari, Sri; Irfan, Andi; Zakaria, Nor Balkish; Mujahidin (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to research the extent of information prevention fraud disclosed at PTKIN throughout Indonesia through a theory agency. Types of research This study is quantitative descriptive with descriptive statistical methods and tests of Kruskal Wallis. Amount of the sample in the study This is 34 PTKINs, categorized as "very good/good "PTKINs. The collection of this data uses the existing information on the PTKIN website. Research data This was analyzed using the SPSS V.23 program. Results study. This shows that based on an analysis of content information prevention fraud revealed on the website, each PTKIN uses the Fraud Prevention Disclosure Index (FPDI), which found that PTKIN in Indonesia, on average, reveals 79 items out of 100 FPDI items. Overall, the level of disclosure for PTKIN in Indonesia is sufficient. PTKIN in Indonesia is already Very strong in Index Disclosure Prevention Fraud, including integrity, rules, internal audit, core values, scholarship, maintenance awareness, procedures, response research, and prevention strategies fraud.